EDIBLE FILM FUNCTIONAL OF BANANA PEEL AND CHICKEN EGG FLOUR WITH CINNAMON LEAF (Cinnamomum burmanii) EXTRACT - Nor Asiyah; Agata Febby Ayuningtyas; Fitri Halisyah; Iryanti Fatyasari Nata (Universitas Lambung Mangkurat, 2020)
The biggest obstacle to the food industry is the limited shelf life of products. One approach to reduce this problem is by using edible film. Edible film is a thin layer that can be consumed and as a protective food material against the environment such as water vapor, oxygen, and air humidity. This study aims to evaluate the edible film made in terms of the mass composition of chicken egg shell flour and banana peel flour, determine the optimum composition of the addition of cinnamon leaf extract (Cinnamomum burmanii) as a source of antioxidants, test the physical and chemical properties and the ability to apply the resulting edible film. Edible film was made from a mixture of chicken eggshell flour (5%, 10%, 15% w/w) and banana peel pectin (6 g) in distilled water (93.5 mL), then added with cinnamon leaf extract with various compositions (0.025). %, 0.050%, 0.075%, 0.10% v/v) then added glycerol (1.5 g). The mixture was heated to a temperature of ± 96 0C, 1000 rpm for 40 minutes. The best composition of the edible film produced with 10% chicken eggshell flour containing 0.10% cinnamon leaf extract. The benefits of this functional edible film can help to extend the shelf life of food and be environmentally friendly.